Evoluzione dei sistemi GNSS (GEOmedia, 2010)
Evolution of GNSS systemsWith this article GEOmedia is starting a review on the latest updates concerning GNSS technology. Since the first GPS satellites, the evolution of GNSS sector witnessed the grow of other constellations: GLONASS, Beidou (Compass) and Galileo. The development of positioning techniques even brought to the creation of specific Augmentation Systems, capable of the enhancement of the localization signals (GBAS and SBAS). The aim of this review is to provide a general-to-particular knowledge of all the positiong and augmentation systems, from a historical point of view to real applications.